CAPE and its synthetic derivative VP961 restore BACH1/NRF2 axis in Down Syndrome - Pagnotta, Sara; Tramutola, Antonella; Barone, Eugenio; Di Domenico, Fabio; Pittalà, Valeria; Salerno, Loredana; Folgiero, Valentina; Caforio, Matteo; Locatelli, Franco; Petrini, Stefania; Butterfield, D. Allan; Perluigi, Marzia (Free radical biology & medicine, 2022)
The cells possess several mechanisms to counteract the over-production of reactive oxygen species (ROS) and reactive nitrogen species (RNS), including enzymes such as superoxide dismutase, catalase and glutathione peroxidase. Moreover, an important sensor involved in the anti-oxidant response is KEAP1-NRF2-ARE signaling complex. Under oxidative stress (OS), the transcription factor NRF2 can dissociate from the KEAP1-complex in the cytosol and translocate into the nucleus to promote the transcriptional activation of anti-oxidant genes, such as heme oxygenase 1 and NADPH quinone oxidoreductase. Within this context, the activation of NRF2 response is further regulated by BACH1, a transcription repressor, that compete with the KEAP1-NRF2-ARE complex. In this work, we focused on the role of BACH1/NRF2 ratio in the regulation of the anti-oxidant response, proposing their antithetical relation as a valuable target for a therapeutic strategy to test drugs able to exert neuroprotective effects, notably in aging and neurodegenerative diseases. Among these, Down syndrome (DS) is a complex genetic disorder characterized by BACH1 gene triplication that likely results in the impairment of NRF2 causing increased OS. Our results revealed that BACH1 overexpression alters the BACH1/NRF2 ratio in the nucleus and disturbs the induction of antioxidant response genes ultimately resulting in the accumulation of oxidative damage both in Ts2Cje mice (a mouse model of DS) and human DS lymphoblastoid cell lines (LCLs). Based on this evidence, we tested Caffeic Acid Phenethyl Ester (CAPE) and the synthetic analogue VP961, which have been proven to modulate NRF2 activity. We showed that CAPE and VP961 administration to DS LCLs was able to promote NRF2 nuclear translocation, which resulted in the amelioration of antioxidant response. Overall, our study supports the hypothesis that BACH1 triplication in DS subjects is implicated in the alteration of redox homeostasis and therapeutic strategies to overcome this effect are under investigation in our laboratory. [Display omitted] •BACH-1/Nrf-2 has a fundamental role in the regulation of anti-oxidant response.•BACH-1 is among the genes encoded on HSA21 found to be overexpressed in Down Syndrome.•Targeting BACH-1/Nrf-2 axis is a valid therapeutic strategy in disease with increased Oxidative Stress.•Oxidative stress is an early event in Down Syndrome.•CAPE and VP961 are able to restore BACH-1/Nrf-2 axis in Down Syndrome.